A Crisis in Context: Local Conditions, National Events, and Economic Policy Mood. (November 2015) - Newman, Benjamin J.
The effect of economic distress on public opinion is well studied in political science. This research, however, tends to focus on one's personal economic situation or national economic conditions, with considerably less scholarly attention directed toward understanding how intermediate levels, such as citizens' local economic environment, shapes mass economic policy preferences. In response, this article develops a theory of the effect of local economic context on policy preferences which posits national economic events as a moderating factor and views toward the fairness of the economic system as an intervening factor. Drawing upon over a decade of survey data, and focusing on the 2008 Financial Crisis and public views toward business corporations, this article demonstrates that the Crisis polarized citizens across affluent and poor areas with respect to perceptions of corporate-led maldistribution, which in turn, had an indirect polarizing effect on economic policy mood.